LIFE HISTORY ANNELIDA: POLYCHAETA IN AN ESTUARY OF THE OMUTA-GAWA RIVER, KYUSHU, JAPAN - Hanafiah, Zazili (BIOVALENTIA: Biological Research Journal, 2015)
The research was conducted at fourã€€stations in the Omuta-gawa River, Kyushu, Japan from December 2003 to July 2005. The results of the monthly survey clearly indicated that Hediste japonica has one generation per year. The reproductive period of this species is from late December to late February, and also occurred on H. diaroma, that it has one generation per year. The reproductive period of this species in the Omuta-gawa River is from middle December to late April, when reproductive swarming of mature adults occurs. This reproductive period is much longer than that of H. japonica. Both Hediste species, spawning, fertilization and early development occur in water column with a long pelagic larval life.Â Keywords: life history, Hediste japonica, H. diadroma, reproductive period, estuary